Analisis Akuisisi PT. Indofood Sukses Makmur Terhadap PT. Indomarco Adi Prima Sebagai Distributor Makanan Olahan - Ahya Amalia Lutfiana; Esti Rahmandani; Denada Rahmawati; Endang Kartini Panggiarti (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
The purpose of this research is to analyze the acquisition of PT. Indofood Sukses Makmur against PT. Indomarco Adi Prima. This research took PT. Indofood Sukses Makmur as a research object. The research method is literature and interview methods that explain or describe observational data without statistical tests. From the results of the analysis, PT. Indofood Sukses Makmur has a more efficient route for distributing its products to the market with the company PT. Indomarco Adi Prima is an important distributor with a network in almost all regions of Indonesia. Indonesian distributor Indofood Sakmur is an Indonesian Distributor of Indofood Makmur to the best market in Indonesia, Indonesia and Indonesia.